Evaluation of the predictive factors of the short-term effects of a multidisciplinary rehabilitation in COVID-19 survivors. Issue 11 (November 2022) - Barbieri, Valentina; Scarabel, Luca; Bertella, Laura; Scarpina, Federica; Schiavone, Nicola; Perucca, Laura; Rossi, Paolo
Objective: Functional impairments after coronavirus disease 2019 (COVID-19) constitute a major concern in rehabilitative settings; however, evidence assessing the efficacy of rehabilitation programs is lacking. The aim of this study was to verify the clinical characteristics that may represent useful predictors of the short-term effectiveness of multidisciplinary rehabilitation. Methods: In this real-practice retrospective pre–post intervention cohort study, the short-term effectiveness of a multidisciplinary patient-tailored rehabilitation program was assessed through normalized variations in the Functional Independence Measure in post-acute care patients who had overcome severe COVID-19. Biochemical markers, motor and nutritional characteristics, and the level of comorbidity were evaluated as predictors of functional outcome. Length of stay in the rehabilitation ward was also considered. Results: Following rehabilitation, all participants ( n  = 53) reported a significant decrease in the level of disability in both motor and cognitive functioning. However, neither motor and nutritional characteristics nor comorbidities played a significant role in predicting the overall positive change registered after rehabilitation. Conclusions: The results support the existing sparse evidence addressing the importance of an early rehabilitation program for patients who received intensive care and post-acute care due to severe COVID-19.